2006
DOI: 10.1080/15368370601054894
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Absorption in the Head of Adults and Children Due to Mobile Phone Operation Close to the Head

Abstract: The Specific Absorption Rate (SAR) produced by mobile phones in the head of adults and children is simulated using an algorithm based on the Finite Difference Time Domain (FDTD) method. Realistic models of the child and adult head are used. The electromagnetic parameters are fitted to these models. Comparison also are made with the SAR calculated in the children model when using adult human electromagnetic parameters values. Microstrip (or patch) antennas and quarter wavelength monopole antennas are used in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 17 publications
1
21
0
1
Order By: Relevance
“…This contrasts strongly with Bit-Babik et al (2005) , who, again using modelling, concluded that head size was irrelevant and absorption levels were similar for adult and children's heads. The elevated exposure fi ndings of Gandhi are replicated also by modelling by de Salles et al (2006) , who also found that elevations of up to 60% occurred in small heads. Since ownership of mobile phones ranges from 97% of 9+ year-old children in Italy (Dimonte and Ricchiuto, 2006) , 76% in Hungary (Mezei et al, 2007) and 36% in Germany (Bohler and Schuz, 2004) , then consideration of exposure effects is particularly important.…”
Section: The Problemsupporting
confidence: 59%
“…This contrasts strongly with Bit-Babik et al (2005) , who, again using modelling, concluded that head size was irrelevant and absorption levels were similar for adult and children's heads. The elevated exposure fi ndings of Gandhi are replicated also by modelling by de Salles et al (2006) , who also found that elevations of up to 60% occurred in small heads. Since ownership of mobile phones ranges from 97% of 9+ year-old children in Italy (Dimonte and Ricchiuto, 2006) , 76% in Hungary (Mezei et al, 2007) and 36% in Germany (Bohler and Schuz, 2004) , then consideration of exposure effects is particularly important.…”
Section: The Problemsupporting
confidence: 59%
“…For example, children's brains are still undergoing rapid growth and there is the possibility that this may make them more vulnerable to small stressors [Romeo and McEwen, 2006]. There have also been some reports suggesting that children may absorb more EMF than adults due to their different physiognomy [de Salles et al, 2006], however, current research suggests that differences between children and adults are likely to be slight compared to the variances observed within the study [Wiart et al, 2008].…”
Section: Introductionmentioning
confidence: 77%
“…For example, as the child and adolescent years are critical periods for brain and cognitive development (Yurgelun-Todd 2007), there is the possibility that this may make them more vulnerable to small stressors (Romeo and McEwen, 2006). There have also been some reports suggesting that children and adolescents may absorb more EMF than adults due to their different physical characteristics (de Salles et al, 2006). However, current research suggests that differences between children and adults are likely to be slight compared to the variances observed within the study (Wiart et al, 2008).…”
Section: Introductionmentioning
confidence: 82%